Cytotoxicity of sophorolipid-gellan gum-gold nanoparticle conjugates and their doxorubicin loaded derivatives towards human glioma and human glioma stem cell lines - Dhar, Sheetal; Reddy, E. Maheswara; Prabhune, Asmita; Pokharkar, Varsha; Shiras, Anjali; Bhagavatula L. V. Prasad (Nanoscale, 2011)
Biocompatible gold nanoparticles were synthesized by using a naturally occurring gum-Gellan Gum-as a capping and reducing agent. These were further conjugated with sophorolipids which again were accessed through a biochemical transformation of a fatty acid. The cellular uptake of sophorolipid-conjugated gellan gum reduced gold nanoparticles and their cytotoxicity on human glioma cell line LN-229 and human glioma stem cell line HNGC-2 were investigated. Quite surprisingly even the simple sophorolipid-conjugated gellan gum reduced/capped gold nanoparticles showed greater efficacy in killing the glioma cell lines and, gratifyingly, the glioma stem cell lines also. The cytotoxic effects became more prominent once the anti cancer drug doxorubicin hydrochloride was also conjugated to these gold nanoparticles.